AN ANALYSIS OF FISHERIES AND OTHER ECOLOGICAL RESOURCES IN THE SEGMENT OF MEGHNA RIVER IN BANGLADESH (Proceedings of The International Conference on Economics and Development, 2018)
Bangladesh is a riverine country with hundreds of rivers. All of them carry different valuable attributes. However, our present endeavor is to look into a particular segment of mighty Meghna River in Bangladesh which is rich in fishery resources and other ecological objects. It plays a vital role in supplying future water to urban area of Dhaka city also. In this connection a survey was conducted to see the pool of resources specially fisheries resources availability in the river area. It was found that several locations are abundant with fish, aquatic invertebrates, amphibians, reptiles, birds, mammals, and butterfly. A minimum 30 out of 53, red listed fish species are available in the study area which indicates the importance of the river habitat for better management in future. The river is not only rich in fisheries resources but it helps providing lot of other vital services which are important for healthy growth of these resources.  However, this is not the end of the story. For proper valuation we estimated Total Economic Value (TEV) of the objects using direct values, indirect values, existence values and option values. The estimate shows a significant value in the segment and deserves proper management of these resources.
Keywords: fisheries; ecology; total value; management